2023
DOI: 10.1109/ojits.2023.3259283
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model-Based and Control-Aware Communication Strategies for Cooperative Adaptive Cruise Control

Abstract: Utilizing Vehicle-to-everything (V2X) communication technologies, vehicle platooning systems are expected to realize a new paradigm of cooperative driving with higher levels of traffic safety and efficiency. Connected and Autonomous Vehicles (CAVs) need to have proper awareness of the traffic context. The cooperative platoon's performance will be influenced by the communication strategy. In particular, time-triggered or event-triggered are of interest here. The expenses related to communication will increase s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Various methods have been proposed to minimize the tracking error. A few notable ones include simple models such as first and second order kinematic models (constant speed and constant acceleration), to more complex ones that are based on Kalman Filter and Gaussian Process [33][34][35]. Nevertheless, it has been shown that in a longitudinal car-following regime, a second order kinematic model can perform with high accuracy [36].…”
Section: Vehicle Trackingmentioning
confidence: 99%
“…Various methods have been proposed to minimize the tracking error. A few notable ones include simple models such as first and second order kinematic models (constant speed and constant acceleration), to more complex ones that are based on Kalman Filter and Gaussian Process [33][34][35]. Nevertheless, it has been shown that in a longitudinal car-following regime, a second order kinematic model can perform with high accuracy [36].…”
Section: Vehicle Trackingmentioning
confidence: 99%
“…Higher rates of AVs in the future and their ability to communicate with both each other and the environment will influence the distancing behavior between vehicles as well. With the goal of traffic flow optimization for increasing fuel efficiency, platooning will enable vehicles to also maintain closer distances between each other while still ensuring safety [50]- [52].…”
Section: Distancing Behavior In Steady-state Car-followingmentioning
confidence: 99%